NILAI PERUSAHAAN ATAS DAMPAK KEBIJAKAN PENGAMBILAN KEPUTUSAN INVESTASI, PEMBIAYAAN, DEVIDEN, DAN UKURAN PERUSAHAAN PADA INDUSTRI MANUFAKTUR TAHUN 2018–2022 - Wibowo, Budi Satiyo; Nur, Basyiruddin (Politeknik Negeri Lhokseumawe, 2024)
Abstract: The aim of this research is to determine the impact of policies taken by investors based on financial reports published by companies operating in the manufacturing industry, and to find out how much impact the decisions taken have on company value. This research took 52 sample data. The analysis method uses sample data through ratios such as Price Earning Ratio, Debt Equity Ratio, Dividend Payout Ratio, and Company Size, so that the impact that will influence the value of the company can be seen, whether positive or negative.The results of this research, there are several conclusions shown in this research, namely; The impact of investment decision making policies does not have a positive influence on company value. The impact of financing decision-making policies has a positive influence on company value. The impact of company size on decision-making policies on dividends does not have a positive influence on company value. The impact of company size does not have a positive influence on company value.Keywords: Investment, financing, and dividend policies, company size, company value.